2023
DOI: 10.3390/medicina60010045
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Assistant Experience on Perioperative Outcomes of Simple and Radical Laparoscopic Nephrectomy: Does It Really Matter?

Francesca Ambrosini,
Guglielmo Mantica,
Giovanni Marchi
et al.

Abstract: Background and Objectives: While systematic reviews highlight the advantages of laparoscopic nephrectomy over traditional open surgery, the impact of an assistant’s experience on surgical outcomes remains unclear. This study aims to evaluate whether the level of assistant expertise influences laparoscopic nephrectomy outcomes. Materials and Methods: Retrospective data from our institutional database were analyzed for patients who underwent laparoscopic nephrectomy between January 2018 and December 2022. Proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…However, with regard to laparoscopic nephrectomy, some reports have shown that the experience of the assistant does not affect the perioperative outcomes [ 21 ]. However, despite these limitations, there are few studies comparing the prognoses of the transperitoneal approach and the retroperitoneal approach in LNUs, especially in Japan.…”
Section: Discussionmentioning
confidence: 99%
“…However, with regard to laparoscopic nephrectomy, some reports have shown that the experience of the assistant does not affect the perioperative outcomes [ 21 ]. However, despite these limitations, there are few studies comparing the prognoses of the transperitoneal approach and the retroperitoneal approach in LNUs, especially in Japan.…”
Section: Discussionmentioning
confidence: 99%